The role of body mass index-for-age in the assessment of acute malnutrition and obesity in Moroccan hospitalized children - Hassan Barouaca, Dalal Ben Loubir, Bachir El Bouhali, Nabil Tachfouti, Adil El Midaoui (Journal of Applied Pharmaceutical Science, 2021)
The aim of the present study was to examine the accuracy of body mass index-for-age (BMI-Z), mid-upper arm circumference (MUAC), and MUAC z-score (MUAC-Z) in assessing the acute malnutrition as well as the BMI-Z in assessing obesity in Moroccan hospitalized children aged from 1 month to 5 years. This is a longitudinal observational study carried out on 337 children. Weight, height/length, and MUAC related to sex and age were determined at admission and exported to World Health Organization (WHO) Anthro software for conversion to sex-age specific z-score indices. Weighted Cohen’s Kappa test was used to assess the concordance between weight-for-height z-score (WFH-Z), BMI-Z, MUAC-Z, and MUAC in screening for acute malnutrition defined as WFH-Z < –2SD or between WFH-Z and BMI-Z in screening for obesity as defined by WFH-Z > 3SD. The area under the receiver operating characteristic (ROC) area under the curve (AUC) was used to assess the performance of the anthropometric indexes in screening for acute malnutrition. We found high malnutrition prevalence as reflected by wasting (12.17%), stunting (13.35%), overweighting risk (24.64%), overweighting (11.39%), and low malnutrition prevalence as indicated by underweighting (4.75%) and obesity (3.56%). The BMI-Z showed perfect agreement to diagnose acute malnutrition (Kappa = 0.872) and obesity (Kappa = 0.827) with higher sensitivity and specificity indexes as well as higher positive predictive and negative predictive values. The AUC of the BMI-Z revealed very outstanding diagnostic accuracy to assess acute malnutrition (AUC = 0.98) and obesity (AUC = 0.99) in comparison to those of MUAC (AUC = 0.75) and MUAC-Z (AUC = 0.69). The results of the present study suggest that BMI-Z could be a good alternative indicator to assess acute malnutrition and obesity in hospitalized children aged from 1 month to 5 years.
Keywords: Acute malnutrition, anthropometric parameters, obesity, hospitalized children.